Comparison between kinesio tape and sport massage on blood lactate following anaerobic exercise / Amirul Azim Othman - Othman, Amirul Azim (Faculty of Sport Science and Recreation, 2019)
The purpose of this study was to investigate the comparison two different treatment which are kinesiotape and sport massage on lactate level following anerobic exercise among male collegiate UiTM Pahang (n=20) were selected as the sample of the study using purposive sampling technique and will test in two group that are control group that applying kinesiotape and experimental group that be applying sport massage. Measured using blood lactate anaylzer. Statistical analysis of the tests was conducted by using independent paired sample t-test. A set of data was recorded and been analyze. There was no significant effect between kinesio tape and sport massage on lactate level following anerobic exercise because the the p-value is p-> 0.05. The researcher found that not have any significant impact between kinesio tape and sport massage on lactate level taking after anaerobic work out among colligates UiTM Pahang.